The Effect of Progressive Muscle Relaxation Technique on Pain - Irawan, Hendra; Abdillah, Hadi; Alamsyah, Azhar Zulkarnain; Alamsah, Mustopa Saepul (Universitas Prima Indonesia, 2026)
Pain is a common clinical problem that can be managed through both pharmacological and non-pharmacological approaches, including progressive muscle relaxation. This study aimed to examine the effect of progressive muscle relaxation technique on pain among patients in the Fatmawati Ward of RSUD Sekarwangi. A pre-experimental study with a one-group pretest–posttest design was conducted involving 25 respondents selected through purposive sampling, consisting of patients experiencing mild to moderate pain. Progressive muscle relaxation was administered once daily for approximately 15–20 minutes over the intervention period. Pain intensity was measured using the Numeric Rating Scale (NRS) before and after the intervention, and data were analyzed using the Wilcoxon Signed Rank Test. The results showed that prior to the intervention, most patients experienced moderate pain (84%), while after the intervention all patients (100%) reported mild pain. Statistical analysis revealed a significant difference in pain levels before and after the intervention (p = 0.001; < 0.05). These findings indicate that progressive muscle relaxation is effective in reducing pain among hospitalized patients. This technique can be considered a complementary nursing intervention in hospital pain management, and future studies are recommended to involve larger samples, control groups, and longer follow-up periods to evaluate its long-term effectiveness and broader clinical applications.